Regional crop water use assessment using Landsat‐derived evapotranspiration. Issue 1 (27th December 2020) - Bawa, Arun; Senay, Gabriel B.; Kumar, Sandeep
Abstract: Reliable information on water use and availability at basin and field scales are important to ensure the optimized constructive uses of available water resources. This study was conducted with the specific objective to estimate Landsat‐based actual evapotranspiration (ETa) using the Operational Simplified Surface Energy Balance (SSEBop) model across the state of South Dakota (SD), USA for the 1986–2018 (33‐year) period. Validated ETa estimations (r 2 = 0.91, PBIAS = −4%, and %RMSE = 11.8%) were further used to understand the crop water‐use characteristics and existing historic mono‐directional (increasing/decreasing) trends over the eastern (ESD) and western (WSD) regions of SD. The crop water‐use characteristics indicated that the annual cropland water uses across the ESD and WSD were more or less met by the precipitation amounts in the area. The ample water supply and distribution have led to high rainfed and low percentage of irrigated cropland (~2.5%) in the state. The WSD faced greater crop‐water use reductions than the ESD during drought periods. The landscape ETa responses across the state were found to be more sensitive than precipitation for the drought impact assessments. The Mann Kendall trend analysis revealed the absence of a significant trend ( p  > 0.05) in annual ETa at a regional scale due to the varying weather conditions in the state. However, about 12% and 9% cropland areas in the ESD and WSD, respectively, revealed a significant mono‐directional trend at pixel scale ETa. Most of the pixels under significant trend showed an increasing trend that can be explained by the shift in agricultural practices, increased irrigated cropland area, higher productions, moisture regime shifts, and decreased risk of farming in the dry areas. The decreasing trend pixels were clustered in mid‐eastern SD and could be the result of dynamic conversion of wetlands to croplands and decreased irrigation practices in the region. This study also demonstrates the tremendous potential and robustness of the SSEBop model, Landsat imagery, and remote sensing‐based ETa modelling approaches in estimating consistent spatially distributed evapotranspiration. Abstract : Landsat‐based field‐scale actual evapotranspiration (ETa) maps were generated using the SSEBop model across the state of South Dakota (SD), USA for the 1986‐2018 period. Estimated ETa products were further used to understand the crop water‐use characteristics and existing historic mono‐directional (increasing/decreasing) trends over the eastern (subhumid/cropland dominated) and western (semiarid/shrubland dominated) regions of SD. The study demonstrates the tremendous potential and robustness of the SSEBop model, Landsat imagery, and remote sensing‐based ETa modeling approaches in estimating consistent spatially distributed evapotranspiration.